2015
DOI: 10.1002/ajp.22445
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses to novelty by wild and captive orangutans

Abstract: Several studies have suggested that wild primates tend to behave with caution toward novelty, whereas captive primates are thought to be less neophobic, more exploratory, and more innovative. However, few studies have systematically compared captive and wild individuals of the same species to document this "captivity effect" in greater detail. Here we report the responses of both wild and captive orangutans to the same novel items. Novel objects were presented to wild orangutans on multiple platforms placed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 70 publications
1
95
2
Order By: Relevance
“…Small platforms in the shape of ape nests were hoisted into the canopy within the height range of orangutan travel and provided with novel items, including novel foods. The results [52] showed that wild orangutans, both Sumatran and Bornean, pass the novel stimulus at a safe distance and avoid approaching novelty for several months (figure 1). In both the Sumatran and the Bornean site, only a single (adolescent) individual was ever recorded as contacting the novel items, despite their being available for nearly five and over eight months, respectively.…”
Section: How Wild Orangutans Acquire Their Innovationsmentioning
confidence: 97%
See 4 more Smart Citations
“…Small platforms in the shape of ape nests were hoisted into the canopy within the height range of orangutan travel and provided with novel items, including novel foods. The results [52] showed that wild orangutans, both Sumatran and Bornean, pass the novel stimulus at a safe distance and avoid approaching novelty for several months (figure 1). In both the Sumatran and the Bornean site, only a single (adolescent) individual was ever recorded as contacting the novel items, despite their being available for nearly five and over eight months, respectively.…”
Section: How Wild Orangutans Acquire Their Innovationsmentioning
confidence: 97%
“…The same study that examined responses to novelty in wild orangutans was repeated with zoo animals using the same and very similar sets of novel items [52]. The contrast was striking (figure 1).…”
Section: Orangutans In Zoos and Rescue Centresmentioning
confidence: 97%
See 3 more Smart Citations